KONTESTASI PARADIGMA EKOLOGI POLITIK DALAM KONFLIK AGRARIA - Mahtia Safitri; Ismar Hamid (Universitas Lambung Mangkurat, 2023)
The agrarian conflict occurred in Kintapura Village, Kintap District, Tanah Laut Regency. This study aims to analyze the agrarian conflict by using the perspective of conflict and contestation of the political ecology paradigm. This study uses a qualitative research method with a case study approach. Data collection techniques used were participant observation, in-depth interviews, and documentation. The results showed that the agrarian conflict has made the village an arena for contesting the political ecology paradigm and has had an impact on the existence of unsustainable natural resource management. The eco-developmentalism paradigm in the form of coal mines and oil palm plantations; the eco-conservationism paradigm through the policy of designating convertible production forest areas (HPK); and, people's livelihood as a manifestation of the eco-populist paradigm. The existence of these three paradigms in the management of natural resources has given rise to agrarian conflicts. Natural resource management policies are dominated by the class that has power, namely the owners of capital (the bourgeoisie) and landlords represented by coal mining companies and oil palm plantations. The ruling class then influences policy makers who use their political power in establishing natural resource management policies through the camouflage of eco-conservationism policies, namely the designation of convertible production forest areas (HPK). The class that suffered the most was the farming class which lost its land under management and gave birth to a new class, namely farm laborers and poor farmers.